SPE Annual Technical Conference and Exhibition 1993
DOI: 10.2118/26642-ms
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Modelling of Asphaltene Precipitation

Abstract: An efficient modelling technique based on the representation of the precipitated asphaltene as a pure dense phase is presented. The success of the approach is based on the division of the heaviest component in the oil into a nonprecipitating and a precipitating component.The characterization of these components is discussed. This model was able to make quantitative predictions of experimental data from the literature as well as additional data from industry. This was achieved with only a small number of adjust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
83
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(84 citation statements)
references
References 11 publications
0
83
0
1
Order By: Relevance
“…The fourth model is solid model in which the solid phase is considered as two main parts, precipitating and non-precipitating asphaltene. There are too many matching parameters needed to tune this model with the experimental data [36].…”
Section: Dimensionless Eos Parametermentioning
confidence: 99%
See 1 more Smart Citation
“…The fourth model is solid model in which the solid phase is considered as two main parts, precipitating and non-precipitating asphaltene. There are too many matching parameters needed to tune this model with the experimental data [36].…”
Section: Dimensionless Eos Parametermentioning
confidence: 99%
“…The reference fugacity could be calculated from a data point on the asphaltene precipitation envelope (APE) [46].…”
Section: Asphaltene Componentmentioning
confidence: 99%
“…Waste minimization and cleanup have become the focus It has been suggested that the asphaltenes tend to form of environmental policies in the petroleum industry (2)(3)(4)(5)(6)(7)(8). aggregates which have an adsorbed covering sheath of aroAs a preliminary step during refinery treatment, crude oils matic resins as a stabilizing layer (43)(44)(45). These proposed are normally desalted to remove species such as chloride interactions between the resins and asphaltenes are illussalts which poison refinery catalysts and enhance corrosion trated in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Thermodynamic-colloidal model is the usable approach that has been introduced by Leontarities and Mansoori (1987) for asphaltene flocculation. This model is more applicable to situations where there is a dissociation of the asphaltene/resin micelles (Nghiem et al, 1993). Asphaltene aggregates are assumed to be stabilized by a layer of resins and the precipitation of asphaltene is thermodynamically irreversible.…”
Section: Introductionmentioning
confidence: 99%